2017
DOI: 10.1155/2017/1485283
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species‐Mediated Mechanisms of Action of Targeted Cancer Therapy

Abstract: Targeted cancer therapies, involving tyrosine kinase inhibitors and monoclonal antibodies, for example, have recently led to substantial prolongation of survival in many metastatic cancers. Compared with traditional chemotherapy and radiotherapy, where reactive oxygen species (ROS) have been directly linked to the mediation of cytotoxic effects and adverse events, the field of oxidative stress regulation is still emerging in targeted cancer therapies. Here, we provide a comprehensive review regarding the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 92 publications
5
94
0
2
Order By: Relevance
“…A mild increase in ROS can lead to an adaptive survival response, including expression of NRF2 to increase GSH production, whereas a severe increase in ROS can trigger apoptosis. Hence, it has been recognized for some time that cancer cells are potentially vulnerable to treatments that enhance ROS levels and cause cell death (Trachootham et al, 2009;Kim et al, 2016;Chio and Tuveson, 2017;Teppo et al, 2017;Moloney and Cotter, 2018). Several strategies have been employed to induce ROS, including ionizing radiation, inhibition of the ubiquitin-proteasome pathway, and perturbing GSH, glucose, and glutamine metabolism (Gorrini et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A mild increase in ROS can lead to an adaptive survival response, including expression of NRF2 to increase GSH production, whereas a severe increase in ROS can trigger apoptosis. Hence, it has been recognized for some time that cancer cells are potentially vulnerable to treatments that enhance ROS levels and cause cell death (Trachootham et al, 2009;Kim et al, 2016;Chio and Tuveson, 2017;Teppo et al, 2017;Moloney and Cotter, 2018). Several strategies have been employed to induce ROS, including ionizing radiation, inhibition of the ubiquitin-proteasome pathway, and perturbing GSH, glucose, and glutamine metabolism (Gorrini et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding metastatic ccRCC, several targeted therapies against VEGF have been approved, including sorafenib, sunitinib, pazopanib and axitinib [1]. Recently, it has been shown that some of these drugs also affect cellular redox homeostasis, beside their primary antitumor role [48]. In contrast to sorafenib, which shows prooxidant effects by a decrease in GSH level [49], sunitinib exhibits antioxidant effects via increase in GSH level and inhibition of neuronal nitric oxide synthase activity (NOS) [50].…”
Section: Discussionmentioning
confidence: 99%
“…For ROS generation by DKP-073, NOX enzymes may be involved as suggested by two used NOX inhibitors. The critical role of ROS in apoptosis regulation in melanoma cells was also seen, when other therapeutic strategies were applied, as chemotherapy and radiotherapy, 48 elesclomol, 49 PI3K inhibition, 12 or BRAF inhibition. 11…”
Section: Discussionmentioning
confidence: 95%